Evaluation of the yield in sawnwood of Eucalyptus benthamii and Eucalyptus grandis by tangential and radial sawing Avaliação do rendimento em madeira serrada de Eucalyptus benthamii e de Eucalyptus grandis por meio do desdobro tangencial e radial - Franca M.C.* (2015)
The aim was to determine the yield of Eucalyptus benthamii and Eucalyptus grandis in the process of the sawing. The methodology involved two diameter classes (20-25 cm and 25.1-30 cm) and two systems sawing (tangential and radial). The yield of sawing was obtained through the relationship between the volume of logs and lumber, being separated into gross yield, no splits, no trimming and liquid. The analysis yield was adopted the Analysis of Variance and Tukey test. The results demonstrated that the system of tangential sawing showed better utilization of raw-material. The treatments consisted of the E. benthamii and tangential system presented the greatest yield reduction due to the removal of parts of the split pieces, while for the loss due to destopo, the percentages found were similar for both species. In the final yield of the process, there was no reduction of yield in lumber with the increase of the diameter of the logs for both species.